2002
DOI: 10.1034/j.1600-0722.2002.21384.x
|View full text |Cite
|
Sign up to set email alerts
|

On the role of MT1‐MMP, a matrix metalloproteinase essential to collagen remodeling, in murine molar eruption and root growth

Abstract: Although the connective tissues of the periodontium are subject to a high turnover rate, no conclusive evidence has yet emerged that periodontal collagen turnover is essential for the eruption of teeth or for root elongation. These processes were studied in mice deficient in MT1-MMP, a membrane type matrix metalloproteinase essential for remodeling of soft tissue-hard tissue interfaces. Mandibular first molars of deficient mice and their wild-type littermates were subjected to stereological analysis in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
16

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 17 publications
(25 reference statements)
2
41
0
16
Order By: Relevance
“…5D) and mutant mice display progressive fibrosis with extensive resorption of alveolar bone in response to the deficient remodeling of the ligament and ligament bone interface. Formation and longitudinal growth of the roots are severely stunted and as a result the molars fail to erupt and remain submerged in the jaws throughout life (Beertsen et al, 2002). Incisors, on the other hand, continuously develop and erupt unimpeded suggesting, somewhat surprisingly, that the periodontal ligament remodeling required for incisor eruption is independent of MT1-MMP.…”
Section: Molar Root Formation and Eruption Are Mt1-mmp Dependentmentioning
confidence: 99%
“…5D) and mutant mice display progressive fibrosis with extensive resorption of alveolar bone in response to the deficient remodeling of the ligament and ligament bone interface. Formation and longitudinal growth of the roots are severely stunted and as a result the molars fail to erupt and remain submerged in the jaws throughout life (Beertsen et al, 2002). Incisors, on the other hand, continuously develop and erupt unimpeded suggesting, somewhat surprisingly, that the periodontal ligament remodeling required for incisor eruption is independent of MT1-MMP.…”
Section: Molar Root Formation and Eruption Are Mt1-mmp Dependentmentioning
confidence: 99%
“…Some studies have suggested that the abnormal expression of MMPs in animal models may be related to the delayed eruption of teeth. Mice deficient in membrane-type 1-MMP show delayed tooth eruption (10,14). MMP-8 is widely expressed in the periodontium during tooth eruption, and its expression may be coordinated with that of collagens types I and III (15).…”
Section: Discussionmentioning
confidence: 99%
“…For example, MT1-MMP is a membrane-bound matrix metalloproteinase, which has been shown to be involved in pericellular matrix digestion by activating a pro-metalloproteinase, presumably pro-MMP-2 (9). Deficiency of MT1-MMP results in inhibition of both root development and tooth eruption (10). Therefore, proper remodeling of the connective tissue is essential for tooth eruption (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van het enzym collagenase werd aangetoond dat het niet betrokken was bij deze route van afbraak. Jaren later bleek dat een ander matrixmetalloproteïnase wel een rol speelt in dit proces, namelijk het membraangebonden matrixmetalloproteïnase-14 (Beertsen et al, 2002).…”
Section: Praktijktoepassingunclassified